Penerapan Model Problem Based Learning dengan Bantuan Media “Cube AR” Kubus Satuan Bermuatan Augmented Reality dalam Peningkatan Pemahaman Siswa pada Materi Volume Kelas V - Damayanti, Rita; Purwati, Panca Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to describe the application of the Problem Based Learning model with the help of the "Cube AR" learning media, a unit cube containing Augmented Reality (AR) in improving class V students' understanding of volume material. Apart from that, this research is also to describe the advantages of implementing the Problem Based Learning model with the help of the "Cube AR" learning media in increasing students' understanding of volume material. The population in this study was class V students at SD Negeri 02 Gisikdrono, totaling 20 students. The research design used is descriptive qualitative. The data collection techniques are observation, documentation and tests. The results of the research show that there is a significant difference between the results of students' conceptual understanding tests before and after learning with the "Cube AR" media. The average pretest score increased from only 63.5 to 77 during the posttest. This shows that the implementation of the "Cube AR" media is effective in increasing students' understanding of volume material.